Bibliometric Analysis of Influencer Phenomenon - Loso Judijanto (West Science Social and Humanities Studies, 2026)
This study presents a bibliometric analysis of the academic literature surrounding the influencer phenomenon, focusing on its development, key themes, and emerging trends in influencer marketing. By utilizing citation analysis, co-authorship networks, and keyword co-occurrence mapping, the study identifies the most influential works and authors within this field, while mapping the evolution of key research topics. Central themes such as social media, influencer marketing, and authenticity dominate the literature, with newer areas of interest, including virtual influencers, artificial intelligence, and the psychological effects of influencer content, beginning to emerge. This paper contributes to understanding the interdisciplinary nature of influencer research and offers insights into the direction of future studies, emphasizing the growing significance of technological advancements and ethical considerations in influencer marketing.